THE HISTORY OF FORMATION OF THE BASIC SCIENTIFIC APPROACHES TO STAFF DEVELOPMENT IN THE ORGANIZATION - I. Temnova (Вестник университета)
In the article we demonstrate the evolution of the views of staff and personnel development from the late 19th century to the present. Some approaches to staff development were considered in the context of scientific schools of management. The main trends of the staff development in today’s companies are shown in this article too.